Technology Systems and Management First International Conference, ICTSM 2011, Mumbai, India, February 25-27, 2011. Selected Papers - Shah, Ketan; Lakshmi Gorty, V. R.; Phirke, Ajay.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the First International Conference on Technology Systems and Management, ICTSM 2011, held in Mumbai, India, in February 2011. The 47 revised full papers presented were carefully reviewed and selected from 276 submissions. The papers are organized in topical sections on computer engineering and information technology; electronics and telecommunication; as well as technology management.
Keywords: Computer science; Computer network architectures; Software engineering; Information systems; Computer engineering; Telecommunication; Computer Science; Computer Systems Organization and Communication Networks; Software Engineering/Programming and Operating Systems; Information Systems and Communication Service; Computer Appl. in Administrative Data Processing; Communications Engineering, Networks; Electrical Engineering